Late Antiquity: The Roman Empire and the monetary representations - Carlan, Cláudio Umpierre (Romanitas - Revista de Estudos Grecolatinos, 2016)
The article begins with a description of the iconography as document history. The image in Antiquity had a specific function: to present a particular social group, mostly illiterate, something that represented the edge of power. It not only legitimized an emperor or king, but was a kind of propaganda.
Keywords: Late Antiquity; Coinage; Power; Rome; Iconography